2011
DOI: 10.2105/ajph.2011.300223
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 2009 Pandemic Influenza A (H1N1)–Related Hospitalization and Death Among Racial/Ethnic Groups in New Mexico

Abstract: This analysis supports recent national efforts to include American Indian/Alaska Native race as a group at high risk for complications of influenza with respect to vaccination and antiviral treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 20 publications
8
89
0
2
Order By: Relevance
“…Hospitalization rates among Native Americans, non-Hispanic Blacks, and Hispanics were 2–6 times higher than those observed among non-Hispanic Whites, which is in agreement with an analysis of hospitalized patients during the 2009 A/H1N1 influenza pandemic in Wisconsin, New Mexico, and the US overall [9, 14, 15]. While Asians experienced the lowest A/H1N1 hospitalization rates among ethnic/race groups, this group showed a statistically significant increased risk of death in the hospital (OR = 23.3) after adjustment for other covariates.…”
Section: Discussionsupporting
confidence: 85%
“…Hospitalization rates among Native Americans, non-Hispanic Blacks, and Hispanics were 2–6 times higher than those observed among non-Hispanic Whites, which is in agreement with an analysis of hospitalized patients during the 2009 A/H1N1 influenza pandemic in Wisconsin, New Mexico, and the US overall [9, 14, 15]. While Asians experienced the lowest A/H1N1 hospitalization rates among ethnic/race groups, this group showed a statistically significant increased risk of death in the hospital (OR = 23.3) after adjustment for other covariates.…”
Section: Discussionsupporting
confidence: 85%
“…[185][186][187][188] One was a German study of 93 critically ill children; 185 another was a UK study of 1520 hospitalised patients of all ages; 186 another was a Canadian study 187 of 605 critically ill adults; and the last study 188 was a US study of 926 hospitalised patients of all ages. After removing data from patients who received zanamivir and patients with missing death status (n = 73, 2%), we had data for 3071 patients, of whom 242 (8%) died, 1803 (59%) were discharged, 140 (4%) remained in hospital and 886 (29%) had missing date of discharge.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…The percentages of missing data were smaller for the deaths than the survivors (0.4% vs. 36% for time to death/discharge for example), suggesting that data collection was more thorough for patients who died. 210 Poeppl 2011 198 Blumental 2011 202 Yung 2011 195 Altmann 2011 185 Enstone 2011 192 del Rosal 2011 205 Nguyen-Van-Tam 2010 186 Thompson 2011 188 Miranda-Choque 2011 197 Yokota 2011 200 Moretti 2011 208 Yang 2010 191 Mickienė 2011 Results show that when the time-dependent nature of treatment is taken into account appropriately the treatment effects change direction, although none of the results is statistically significant. Adjusting for potential confounders and imputing missing data made little difference to the results.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…Although the demographic profiles of patients pre and during the H1N1 were similar, our results reveal that significantly different patterns of clinical presentation (including chief complaint and level of acuity) emerged during the H1N1 epidemic. Published studies, which included adult ED encounters, demonstrated some differences in symptom patterns when comparing patients of pandemic novel H1N1 and seasonal influenza 21,22. Tang et al21 reported a lower incidence of fever and dyspnea in early H1N1 pandemic in Singapore, while Shiley et al22 documented cough and myalgias were more common in patients with a diagnosis of pandemic H1N1 at 2 medical centers in Philadelphia.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies, which included adult ED encounters, demonstrated some differences in symptom patterns when comparing patients of pandemic novel H1N1 and seasonal influenza 21,22. Tang et al21 reported a lower incidence of fever and dyspnea in early H1N1 pandemic in Singapore, while Shiley et al22 documented cough and myalgias were more common in patients with a diagnosis of pandemic H1N1 at 2 medical centers in Philadelphia. Our findings that rates of hospital admission did not differ between the pre H1N1 and post H1N1 groups is consistent with U.S. CDC surveillance data, which do not show an increase in pneumonia and influenza mortality after the emergence of H1N1 21…”
Section: Discussionmentioning
confidence: 99%